LEAN, GREEN, AND THE QUEST FOR SUPERIOR ENVIRONMENTAL PERFORMANCE - ROTHENBERG, SANDRA; PIL, FRITS K.; MAXWELL, JAMES (Production and Operations Management, 2001)
We examine the relationship between lean manufacturing practices and environmental performance as measured in terms of air emissions and resource use. We draw on two unique surveys of 31 automobile assembly plants in North America and Japan, which contain information on manufacturing practice and environmental performance, as well as in‐depth interviews with 156 plant level employees at 17 assembly plants. Our survey results and interviews suggest that lean management and reduction of air emissions of volatile organic compounds (vocs) are associated negatively. Lean manufacturing practices contribute to more efficient use of paints and cleaning solvents, but these in‐process changes are not sufficient to meet the most stringent air regulations. We found some evidence to support the link between lean practices and resource efficiency. While our survey results were in hypothesized direction, they were not statistically significant. In‐depth semi‐structured interviews, however, suggest a more robust relationship, and we use them to describe some mechanisms by which all three aspects of lean management (buffer minimization, work systems, and human resource management) may be related to environmental management practices and performance.